Parental Involvement, Engagement and Partnership in their Children’s Education during the Primary School Years. - O'Toole, Leah; Kiely, Joan; McGillacuddy, Deirdre; O’Brien, Emma Zara; O’Keeffe, Clíona (National Parents Council, 2019)
The current literature review was commissioned by the National Council for Curriculum and Assessment (NCCA) and the National Parents Council Primary (NPC) to examine parental involvement, engagement and partnership in their children’s education in the primary years. It draws on a range of national and international research, analysed through a bioecological lens, to investigate the following research questions: 1. What are the features of good parent-school partnerships during the primary school years focusing, in particular, on supporting all children’s learning? 2. What role does homework play, if any, in helping parents to engage with their children’s learning during the primary school years? 3. What are the key implications for: • Curriculum development? • For those working with parents in support roles?
Keywords: Research Subject Categories::SOCIAL SCIENCES; Education; Primary Education; Parental involvement; School assessment; NCCA; Curriculum development; Child development; Early childhood education--Parent participation; Education--Parent participation; Parent involvement in primary education; Homework; Education--Ireland